2013
DOI: 10.1097/jpo.0b013e31827afedd
|View full text |Cite
|
Sign up to set email alerts
|

Crawling Kinematics in an Early Knee Protocol for Pediatric Prosthetic Prescription

Abstract: Traditionally, young children with limb loss who require a prosthetic knee have been fitted with a prosthesis that does not flex at the knee until they have achieved unaided walking without knee function. This study assessed the effects of an Early Knee protocol, in which children received an articulating prosthetic knee in their first prosthesis, as many as 3 years before the conventional protocol would dictate. Motion analysis was conducted on five children who crawled with a prosthetic knee operating normal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Children with amputations or limb differences through or above the knee can now be fitted with a prosthetic knee relatively early, even while still crawling. 29,30 Multiple pediatric-sized knees can be used as soon as the child and family are ready for them, but there is still not an ideally designed infant-sized knee for transitioning from crawling to walking. After moving through the toddler phase, children generally progress to faster walking and running.…”
Section: Technological Advancesmentioning
confidence: 99%
“…Children with amputations or limb differences through or above the knee can now be fitted with a prosthetic knee relatively early, even while still crawling. 29,30 Multiple pediatric-sized knees can be used as soon as the child and family are ready for them, but there is still not an ideally designed infant-sized knee for transitioning from crawling to walking. After moving through the toddler phase, children generally progress to faster walking and running.…”
Section: Technological Advancesmentioning
confidence: 99%
“…New research has demonstrated that early fitting of a prosthetic knee, as the child pulls to a stand, can provide significant advantages in childhood development by allowing the patient to tall kneel and reciprocally crawl. 17 When do you fit a non-articulated, body-powered, versus myoelectric upper limb prosthesis?…”
Section: Table 2 Questions That Physicians Askmentioning
confidence: 99%
“…Geil et al showed that infants with limb loss using a prosthetic knee locked in extension crawled with slower velocity and reduced cadence. However, a more typical "step-through" crawling pattern was seen in the unlocked knee condition, with less asymmetry [13,14]. Geil and Coulter showed that clearance adaptations were reduced in the EK protocol, and that children achieved an average of 70.4˚swing phase knee flexion in the articulated prosthesis side [12].…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, an "Early Knee" (EK) protocol prescribes an articulating knee joint in the child's first prosthesis, usually when the child achieves pull-to-stand around 12 to 18 months of age. The knee is a free-swinging joint with no active extension assistance or stance control [12][13][14][15]. Previous research has shown biomechanical advantages of the EK protocol.…”
Section: Introductionmentioning
confidence: 99%